A Literature Review of Conflict Resolution - Midhio, I Wayan; Madjid, M. Adnan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2015)
Conflict Resolution in Natural Resources and Teritorial Disputes ‘could’ mediate without any intervention from International Commitee, however that process ultimately oriented to empower legal mechanisms other than court proceedings. Thus, expected does happen to win-lose solution if it occurs when a problem is always brought to court. Most of the natural resource conflicts and territorial disputes that existed today are not only come from the interests but also the influence of our historical background, and as civilized person we should avoid any disrupted action between the parties that involved in the natural resources conflicts and territorial disputes and had to have consulted all issues together, instead use of Military Power to Solve the problems.